Pengaruh CAR, NPF, dan FDR Terhadap Profitabilitas di Bank BNI Syariah Tahun 2013-2020 - Ihsani, Azhar; Yudiantoro, Deny (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This study aims to analyze the effect of CAR, NPF, and FDR on profitability at BNI Syariah Bank. This research design is an associative quantitative research. The data used is secondary data on quarterly financial statements from 2013-2020, which includes 32 data. The data analysis method used is the classical assumption test, and the hypothesis test with multiple linear regression analysis. The results showed that partially CAR had no effect on Profitability, while NPF, and FDR partially affected Profitability at BNI Syariah Bank. Simultaneous research results through the F test show that CAR, NPF, and FDR also affect Profitability at BNI Syariah Bank.